Enhancing older adult financial decision making through the use of self-evaluation worksheets - Denburg, Natalie L.; Collins, Sam M.; Garcia, Norma P.; Cole, Prescott (Frontiers in Psychology, 2022)
Financial products and options are frequently complex and difficult for consumers to understand, which, alongside positively oriented sales pitches and predatory practices, may lead to uninformed and hazardous financial decisions. While several legal reforms have been implemented to improve consumers’ understanding of financial products, these modifications have only achieved mixed results. An ongoing challenge is the passive nature of such modifications, giving rise to confirmation bias—noticing the information which confirms one’s belief about a product, while ignoring or not paying enough attention to the potential risks. The aim of this study was to test an implementable form of public policy to help older adults successfully navigate these financial decisions. We tested whether a self-evaluation worksheet (in conjunction with a written disclosure), involving an active manipulation of financial content, would significantly impact older adult participants’ responses in an experimental reverse mortgage scenario. Forty community-dwelling, healthy older adults were randomized to one of two conditions: Control Condition (passive manipulation of financial content) and Manipulation Condition (active manipulation of financial content). In addition to completing a comprehensive neuropsychological examination, participants were administered the Reverse Mortgage Task (RM Task). Results indicated that a simple yet active manipulation—imparting accurate and understandable information regarding a complex financial product that must be further manipulated—led to the following among participants in the Manipulation Condition: (1) declines in mood; (2) superior understanding of the financial product; and (3) reduced intention of purchasing the financial product. In order for older adults to be well informed about reverse mortgages, policies must be put in place to ensure that adequate and accurate information has been not only provided but also actively processed by the individual.